Robust H∞ static output feedback stabilization of T-S fuzzy systems subject to actuator saturation - Saifia, Dounia; Chadli, Mohammed; Labiod, Salim; Guerra, Thierry Marie (International journal of control, automation, and systems, 2012)
This paper proposes a method for designing robust H ∞ static output feedback stabilization of Takagi-Sugeno (T-S) fuzzy systems under actuator saturation. In this paper, the input saturation is represented by a polytopic model and the modeling error is assumed a norm-bounded uncertainty. A set invariance condition for robust H ∞ static output feedback system under actuator saturation is first established. Then, the estimation of the largest domain of attraction for the system is formulated and solved as a Linear Matrix Inequality (LMI) optimization problem. Two examples are used to demonstrate the effectiveness of the proposed design method.